Response to intramuscular methyl prednisolone in inflammatory hand pain: evidence for a targeted clinical, ultrasonographic and therapeutic approach. Issue 5 (24th November 2006) - Karim, Zunaid; Quinn, Mark A; Wakefield, Richard J; Brown, Andrew K; Green, Michael J; Hensor, Elizabeth M A; Conaghan, Philip G; Emery, Paul
Abstract : Background: Hand pain with stiffness is a common clinical presentation to early arthritis clinics, with outcome varying from resolution to the development of rheumatoid arthritis. Objective: To assess the response and predictors of response to intramuscular methylprednisolone (MP) and hydroxychloroquine (HCQ) using a standardised treatment protocol. Methods: Patients with inflammatory hand pain (IHP), defined as predominantly hand pain and morning stiffness of at least 30 min duration, received a standardised assessment prior to receiving intramuscular MP. Response (primary outcome) at 4 weeks was a 50% improvement in symptoms as perceived by the patient; responders who relapsed received repeat intramuscular MP and HCQ. Results: 102 patients were recruited, of which 21% were rheumatoid factor (RF) positive, 23% had clinical synovitis, 25% had raised C-reactive protein level and 55% had ultrasound-detected synovitis. 73% responded, with associated significant reductions in morning stiffness, Health Assessment Questionnaire, painful and tender joint counts, and visual analogue scores (p⩽0.006 for all). Ultrasound-detected synovitis (p<0.001) and RF (p = 0.04), but not clinical synovitis (p = 0.74), were significantly associated with response to intramuscular MP. 86% who remained on HCQ long term reported a benefit. Conclusions: Patients with IHP have significant improvement in symptoms and function following intramuscular MP. Further placebo-controlled trials are required to assess the role of intramuscular MP and ultrasonography in managing this patient group.